Night shift work increases the risk of developing irritable bowel syndrome: a prospective cohort study in the UK Biobank - Lu, Shiwei; Li, Laifu; Zhuang, Yan; Ye, Fangchen; Zhang, Xinping; Chen, Jiamiao; Sun, Zhuoya; Dai, Fei (Frontiers in Public Health, 2025)
BackgroundIrritable bowel syndrome (IBS) is a functional gastrointestinal disorder associated with a substantial disease burden. Night shift work has become increasingly common and is related to various human diseases. This study investigates the relationship between night shift work and the risk of incident IBS.Methods266,605 participants from the UK Biobank were included in our analysis. Data on shift work patterns, IBS incidence, and relevant covariates were obtained from the UK Biobank. Cox proportional hazard regression models were employed to assess the association between night shift work and IBS risk. Sensitivity analysis and subgroup analysis stratified by specific covariates were conducted to evaluate the robustness of the findings.ResultsDuring a median follow-up of 9.03 years, 5,218 new incident IBS cases were identified. Compared to individuals who never/rarely engaged in night shift work, those who always worked the night shift were associated with an elevated risk of IBS across all models. Specifically, the hazard ratio and 95% confidence interval were 1.41 (1.23–1.60) for Model 1, 1.53 (1.35–1.76) for Model 2, and 1.36 (1.19–1.56) for the fully adjusted Model 3. These results remained consistent in the sensitivity analysis. Subgroup analysis revealed that the increased risk of IBS associated with always night shifts persisted across different genders, age groups, sleep durations, and mental health statuses. However, this association was only observed in individuals with a body mass index (BMI) ≥ 25 kg/m2.ConclusionIndividuals who always worked night shifts exhibited a higher risk of developing IBS compared to those who never/rarely engaged in night shift work.